Metabolic Control of Innate Lymphoid Cell Migration - Willinger, Tim (Frontiers in Immunology, 2019)
Innate lymphoid cells (ILCs) are specialized immune cells that rapidly respond to environmental challenges, such as infection and tissue damage. ILCs play an important role in organ homeostasis, tissue repair, and host defense in the mucosal tissues intestine and lung. ILCs are sentinels of healthy tissue function, yet it is poorly understood how ILCs are recruited, strategically positioned, and maintained within tissues. Accordingly, ILC migration is an area that has recently come into focus and it is important to define the signals that control ILC migration to and within tissues. In this context, signals from the local tissue microenvironment are relevant. For example, ILCs in the intestine are exposed to an environment that is rich in dietary, microbial, and endogenous metabolites. It has been shown that the Vitamin A metabolite retinoic acid promotes ILC1 and ILC3 homing to the intestine. In addition, recent studies have discovered cholesterol metabolites (oxysterols) as a novel class of molecules that regulate ILC migration through the receptor GPR183. ILCs are considered to be largely tissue-resident cells, yet recent data indicate that ILCs actively migrate during inflammation. Furthermore, the discovery of circulating ILC precursors in humans and their presence within tissues has fueled the concept of local ILC-poiesis. However, it is unclear how circulating ILCs enter tissue during embryogenesis and inflammation and how they are directed to local tissue niches. In this review, I will discuss the metabolic signals that regulate ILC homing and their strategic positioning in healthy and inflamed tissues. It is becoming increasingly clear that ILC function is closely linked to their tissue localization. Therefore, understanding the tissue signals that control ILC migration could open new avenues for the treatment of chronic inflammatory diseases.